The Association Between Adverse Child Health, Psychological, Educational and Social Outcomes, and Nondependent Parental Substance: A Rapid Evidence Assessment. (July 2020) - McGovern, Ruth; Gilvarry, Eilish; Addison, Michelle; Alderson, Hayley; Geijer-Simpson, Emma; Lingam, Raghu; Smart, Debbie; Kaner, Eileen
Background: Between 5% and 30% of children in high-income countries live with a substance misusing parent, the majority of which is below dependent levels. However, little is understood about the impact of nondependent parental substance misuse upon children. Methods: We searched the international literature using rigorous systematic methods to identify studies examining parental substance misuse and adverse outcomes in children. The inclusion criteria were cross-sectional, longitudinal, case-control, and cohort studies; of children aged 0–18 years whose parents are high-risk substance misusers; reporting on their health, psychological, substance use, educational, and social outcomes. Results: We identified 36 papers (from 33 unique studies), most of which were assessed as being of medium to high methodological quality ( N = 28). Parental nondependent substance misuse was found to be associated with adversity in children, with strong evidence of an association with externalizing difficulties ( N = 7 papers, all finding an association) and substance use ( N = 23 papers, all finding an association) in adolescents and some evidence of adverse health outcomes in early childhood ( N = 6/8 papers finding an association). There is less evidence of an association between parental substance misuse and adverse educational and social outcomes. The body of evidence was largest for parental alcohol misuse, with research examining the impact of parental illicit drug use being limited. Conclusion: Methodological limitations restrict our ability to make causal inference. Nonetheless, the prevalence of adverse outcomes in children whose parents are nondependent substance misusers highlights the need for practitioners to intervene with this population before a parent has developed substance dependency.